New Mochica and the challenge of reviving an extinct language - Rita Eloranta; Angela Bartens (John Benjamins Publishing Company, 2022)
In this paper, we discuss New Mochica as an example of language revival. New Mochica is definitely not the Mochica of the colonial or republican epoch of present-day Peru and the continuity of an already extinct language can be questioned. Van Coetsem’s (1988, 2000) framework of language contact explains why the contribution of the language revivalists’ dominant language, Spanish, has such a powerful impact on New Mochica, eradicating the central typological features of Mochica. On the other hand, the groups of language revivalists presented in this paper explore the linguistic resources at hand in creative ways. Based on this case study, we propose that language revival should be studied as distinct from language revitalization (cf. Zuckermann & Walsh, 2011), yet as related to overall processes of language making (Hüning & Krämer, 2018).
Keywords: indigenous languages of Peru, language policy and planning, language revival, language making
Variation and Evolution. Aspects of language contact and contrast across the Spanish-speaking world